Uniqueness and Indeterminacy of Equilibria in a Model with Polluting Emissions - Giovanni Bella (Fondazione Eni Enrico Mattei (FEEM), 2006)
Is pollution a dirty word? To answer this question we develop an endogenous growth model à la Rebelo (1991) where dirtiness becomes a fundamental choice variable for the economy to grow. Conclusions to our analysis say that a positive sustainable economic growth is attainable only if polluting production activities are taken into account. Moreover, transitional dynamics points out that local stability and uniqueness of equilibria are also achieved.
Keywords: O41; Q01; Q32; 330; Environmental quality; Endogenous economic growth; Pollution-augmenting technology